INVESTIGATING STUDENTS ACCEPTANCE OF ELEARNING USING TECHNOLOGY ACCEPTANCE MODEL AMONG DIPLOMA IN OFFICE MANAGEMENT AND TECHNOLOGY STUDENTS AT UITM MELAKA - Siti Rosnita Sakarji; Khalijah Binti Mohd Nor; Masliza Mohd. Razali; Nashrah Talib; Nurbarirah Ahmad; Wan Aisyah Amni Wan Mohamad Saferdin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The Industrial Revolution 4.0 (IR 4.0) has given a new impetus to educational transformation. In recent years, education experts recognise the profound impact that a myriad of technological innovations in ICT is having on education. They agree that education 4.0 will be shaped by innovations and will indeed have to train students to produce innovations. E-learning has become an increasingly popular learning approach in higher education institutions (HEIs) due to the rapid growth of Internet technologies in Malaysia. The technology acceptance model (TAM) proposes that perceived ease of use and perceived usefulness predict applications usage. It has been integrated in many university programs and is one of the new learning trends. The study aims to investigate students’ acceptance towards e-learning system using Technology Acceptance Model (TAM). The study was conducted to the students that undergone the Diploma in Office Management and Technology programme from Faculty of Business and Management, UiTM Melaka. The purpose of the study conducted was to investigate the level of students’ acceptance in terms of ease of use and perceived usefulness of e-learning. A set of questionnaires was used for data collection. Descriptive statistics were used to describe the demographic characteristics of the study respondents. All analysis was performed by using SPSS. A total of 50 students completed the survey questionnaire with a satisfactory response rate. It was found that the perceive ease of use and perceived usefulness has a significant effect on attitude toward elearning. The respondents agreed that e-learning is very useful and makes them easier to study the course content. Students are found to be frequently engaged in using e-learning and believed it enhancing their academic performances. The outcomes will enrich the understanding of students’ acceptance of e-learning and will assist in its continuing implementation at UiTM Melaka